Systematic Review of Risk Factors for Equine Colic. (September 2014) - Curtis, L.; Bayes, T.C.; England, G.C.W.; Burford, J.H.; Freeman, S.L.
Abstract : Reasons for performing the study: There are several epidemiological studies that have reported on risk factors for colic, this data has not been systematically reviewed. Objectives: To systematically review the current evidence on risk factors for colic in the horse. Study design: Systematic review in compliance with PRISMA guidelines. Methods: The primary literature search was conducted in CAB Winner of Voorjaarsdagen Award 2014 (1910–2012), Web of Science (1950–2012) and MEDLINE (1946–2012) (between 23–26 November 2012), using the following terms: (horses OR horse OR equine OR equines OR equus OR equidae OR equids OR equid) AND colic. Publications were assessed independently against inclusion criteria (peer‐reviewed articles relating to risk, causes, aetiology or predictors of colic) and exclusion criteria (nongastrointestinal or specific conditions, <3 cases) by LC and SF. Those selected were reviewed using a specifically developed quality assessment criteria (QAC) scoring system. Articles were ranked according to the QAC with those scoring greater than a specific critical threshold considered to be of the highest level of evidence. Results: The search identified 1385 publications; 90 related to risk factors, 36 met the inclusion criteria and were assessed using the QAC. Nine publications were selected for final evaluation. Eight studies were based in the USA, and one multi‐centre study in Europe. Individual papers identified risk factors pertaining to signalment, use of horse, clinical history, diet and other management details; however, there was inconclusive agreement for the majority of factors investigated. Consistent consensus between ≥3 studies identified increasing age, Arab and Thoroughbred breeds, recent change in diet or housing and a previous history of colic as significant risk factors for colic. Conclusions: Evidence for many risk factors is weak and inconsistent, with a variety of confounders and interactions across the studies. There is strong evidence for age, breed, management changes and recent clinical history as risk factors. Ethical animal research:  The study was reviewed and approved by the School of Veterinary Medicine and Science, University of Nottingham Ethics Committee.Sources of funding:  Laila Curtis was funded by the School of Veterinary Medicine and Science, University of Nottingham.Competing interests:  None.